Trust‑based lightweight security protocol for device to device multihop cellular communication (TLwS) - Adnan Shahid, Khan; Yasir, Javed; Johari, Abdullah; Kartinah, Zen (Springer Nature, 2021)
D2D communication is an integral part of LTE-Advance and 5G cellular networks, has gained a lot of popularity in recent years as it ofers high speed, extended coverage, and ubiquitous connectivity. Besides basic function that is direct communication without the need of Base Station (BS), D2D allows small communicating device to act as intermediate device not only for forward the trafcs but also permits the sharing of resources such as spectrum, services, data and social contents for any users that are near the proximity range. With the provision of devices to provide such services and act as authorization devices give rise to vulnerabilities in terms of security and trust, therefore secure mutual authentication is mandatory to mitigate any security threats. In this paper, certifcateless trust based lightweight security scheme (TLWS) for D2D multihop communication is proposed. This proposed scheme utilized elliptic curve and Elgamal cryptosystem assisted with secure hashing algorithm, timestamps, and blindfold challenge for secure communication and key agreements. In addition, we prove that TLWS provides secure mutual authentication using the broadly accepted Burrows–Abadi–Needham logic and shows that the proposed scheme is protected against replay attacks and Man in the middle attack. Overall, TLWS ofers better security and functionality features, and the communicationandcomputationaloverheadsarecomparablewiththerelatedschemes. Therefore, TLWS is applicable to mobile environment efciently.